2010
DOI: 10.1016/s0076-6879(10)75022-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Single Nucleic Acid Molecules with Protein Nanopores

Abstract: We describe the methods used in our laboratory for the analysis of single nucleic acid molecules with protein nanopores. The technical section is preceded by a review of the variety of experiments that can be done with protein nanopores. The end goal of much of this work is single-molecule DNA sequencing, although sequencing is not discussed explicitly here. The technical section covers the equipment required for nucleic acid analysis, the preparation and storage of the necessary materials, and aspects of sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
174
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(176 citation statements)
references
References 81 publications
2
174
0
Order By: Relevance
“…26 Furthermore, it is well known in the literature that the characteristics of polymer translocation through nanopores are dramatically influenced by pore-polymer interactions. 12,[27][28][29][30][31][32][33][34][35] Using simulations in two dimensions, Ikonen et al have shown that the attractive pore-polymer interactions significantly induce resonant activation. 36 Stochastic resonance has been realized 37,38 in several practical situations such as electronic circuits, bistable ring-lasers, sensory processes of crayfish, and voltage-dependent ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…26 Furthermore, it is well known in the literature that the characteristics of polymer translocation through nanopores are dramatically influenced by pore-polymer interactions. 12,[27][28][29][30][31][32][33][34][35] Using simulations in two dimensions, Ikonen et al have shown that the attractive pore-polymer interactions significantly induce resonant activation. 36 Stochastic resonance has been realized 37,38 in several practical situations such as electronic circuits, bistable ring-lasers, sensory processes of crayfish, and voltage-dependent ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,19 The perfusion system was demonstrated using three model systems: (1) a-HL insertion on the cis side, with b-CD blocker introduced to and flushed out of the trans flow channel, (2) a-HL transient blocking with different molecular weight PEGs via the flow channel, and (3) KcsA-E71A proteoliposome fusion from the cis compartment, and concentration-dependent TEA þ blocking of the bilayer-incorporated KcsA mutant from the flow channel. Compared with traditional bilayer electrophysiology systems, 28,29 which use large-volume cups and an aperture in a Teflon septum, both the bilayer and the shunt capacitance are considerably reduced, resulting in higher quality electrical recordings (see supplementary material Fig. S3 (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Each glass chip can hold up to four bilayers, each of which is recorded in parallel, 27 but in this work we use a single aperture. Compared with traditional BLM electrophysiology systems, 11,28,29 both the bilayer and the shunt capacitance are reduced, enabling higher bandwidth low-noise electrical recordings.…”
Section: A Device Design and Fabricationmentioning
confidence: 99%
“…Probably because of the slight anion-selectivity, which has only been observed in reconstituted systems but not in intact cells, DNA can bind inside the channel [81,85]. This binding modulates ion current, which means that single nucleotides bound inside the channel can be identified by the residual current through the alpha-hemolysin pore [101][102][103]. Pulling DNA through nanopores like the alpha-hemolysin channel should in principle allow in the future high throughput sequencing of DNA at low cost.…”
Section: Alpha-hemolysin Of Staphylococcus Aureusmentioning
confidence: 99%